Criminal infiltration in amateur football: the case of the Netherlands - Spapens, Toine (Trends in organized crime, 2025)
In the past five years involvement of criminals in socially beneficial activities and philanthropy has received increasing attention in the Netherlands. Amateur football clubs appear to be particularly vulnerable to criminal infiltration. This paper presents the results of three exploratory studies conducted to answer two main questions. First, to what extent does criminal infiltration in amateur football occur, who are involved and what are their motives? Second, how may criminal infiltration be better prevented, both by clubs and public institutions? Suspected criminals have been active in amateur football as official and covert sponsors, as clubs’ presidents and coaches, or have misused clubs’ facilities for illegal activities. Our studies showed that in 2020, 19% of Dutch amateur football clubs reported to have been confronted with indications of attempted criminal infiltration and in this year the authorities had 40 cases under investigation. Criminal involvement in amateur football can be explained primarily from the perspective of social embeddedness and the aim to improve one’s status and social acceptation within local communities. Although awareness of the problem has been growing, preventing, detecting and tackling criminal infiltration may still be improved.